Stress analysis of the brazing joints of tubular ceramic oxygen-permeable membranes and metal supports. Issue 2 (1st February 2019) - Zhang, Jialu; Zhang, Jian; Li, Lanqian; Zhang, Chao; Zhang, Yuwen; Lu, Xionggang
Abstract: This study investigates the effect of joint structure and temperature dependent mechanical properties on the residual stress states in ceramic/metal brazing joints. A closed-one-end BaCo0.7 Fe0.2 Nb0.1 O3 (BCFN) membrane tube is joined to 310S by using silver filler. Finite element simulation of different BCFN/310S joint assemblies is conducted to evaluate the stresses and deformations of the components at an isothermal state. The results indicate that the outer sleeve structure with low residual stress and good air tightness is more suitable for joining ceramics to metal supports than other joint structures in four joint assemblies. And thermal cycling experiments also verify the functional reliability of the outer sleeve joint assembly. Besides, nonlinear material properties of BCFN can not only cause the sudden change in ceramic stress at 300 °C, but also be the important basis for the stress contrast of different joint structures.